Hidden in the Factors? The Effect of Credit Risk on the Cross-section of Equity Returns - Caren Yinxia Nielsen (Lund University, School of Economics and Management, Department of Economics, 2016)
This paper disentangles the complexity of the distress risk premium in stock returns using the risk-neutral measure of credit risk (valued by CDS spread) and investigates the relationship between credit risk and the market , size, value, and momentum effects. Consistent with the argument for a negative distress premium, firms with higher credit risk have lower stock returns, and a positive value effect is concentrated in high credit quality firms. However, credit risk is positively priced in returns on stocks that won the most in the past year and that, during crisis, co-moved the most with the market. A positive momentum effect is concentrated in high credit risk firms. Furthermore, the size effect, but not the value effect, could be attributed to a positive credit risk effect.
Keywords: G01; G11; G12; 330; Asset pricing; equity returns; size effect; value effect; momentum effect; credit risk effect; credit default swap